COVID-19 and Latinx Disparities: Highlighting the Need for Medical Schools to Consider Accepting DACA Recipients. (19th May 2022) - Lucio, Francisco
Abstract : COVID-19 revealed and magnified the preexisting health inequities faced by many vulnerable groups. The Latinx community is one of these groups and has borne the brunt of disparate rates of infection, hospitalization, and mortality associated with COVID-19. These disparities are rooted in social inequities, such as poverty and lack of access to health care, as well as health inequities associated with disparate disease and condition burdens. Moreover, the lack of an adequate Latinx physician workforce contributes to and exacerbates these inequities. The COVID-19 pandemic has intersected with the U.S. Supreme Court's decision in the Department of Homeland Security v. Regents of the University of California case. The court's decision in this case struck down the attempted ending of the Deferred Action for Childhood Arrivals (DACA) program, although it was settled that the government could end the program if it was done lawfully. Even though this constitutes a win for DACA recipients, the decision is a stopgap as the future of DACA recipients remains vulnerable and subject to other legal challenges and political vagaries. In a time when the need to ameliorate health inequities for the Latinx community is so pronounced, DACA recipient medical trainees could provide much-needed relief. Since the implementation of DACA, some medical schools have decided to accept DACA recipient students, but many do not. This access-limiting practice stymies a group of potential trainees who could help to increase the Latinx physician workforce, as the majority of DACA recipients are Latinx. This article argues that all medical schools should take steps to consider accepting DACA recipient applicants in line with the principles of health equity and suggests 5 recommendations for medical school admissions, support, and advocacy practices.